1993
DOI: 10.1042/cs0850411
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Brain Natriuretic Peptide in Healthy Subjects and Patients with Essential Hypertension: Response to Posture

Abstract: 1. To examine whether posture-induced changes in central volume affect brain natriuretic peptide secretion, plasma levels of human brain natriuretic peptide-32-like immunoreactivity (hBNP-32-li) were measured by radioimmunoassay in 11 healthy subjects and 20 patients with essential hypertension after 15 min supine, 15 min sitting and 15 min with the legs raised at 60°, together with plasma atrial natriuretic peptide concentration, plasma renin activity and plasma aldosterone concentration. 2. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…They have a similar spectrum of biological actions, including diuretic, natriuretic, hypotensive and smooth muscle relaxant ac tivities, and inhibition of the renin-aldosterone axis [1,12], On the other hand, BNP has lesser affinity than ANP for NPR-C (clearance receptors) and it is less susceptible to degradation by endopeptidases-24.11 [2,13], resulting in a longer half-life [2], In their report, describing the isolation and sequence determination of BNP from porcine brain, Sudoh et al [ 12] also showed that this substance was as active as ANP in inducing relaxation of smooth muscle cells and hyotension in the anesthetized rat. These data have been con firmed by several animal studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], The cardiovascu lar effects of BNP in humans were investigated by Yoshi- mura et al [19], who administered synthetic human BNP (0.1 pg/kg-min for 30 min) to healthy subjects and pa tients with congestive heart failure. In healthy subjects, BNP infusion significantly increased the cardiac index and decreased PVR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have a similar spectrum of biological actions, including diuretic, natriuretic, hypotensive and smooth muscle relaxant ac tivities, and inhibition of the renin-aldosterone axis [1,12], On the other hand, BNP has lesser affinity than ANP for NPR-C (clearance receptors) and it is less susceptible to degradation by endopeptidases-24.11 [2,13], resulting in a longer half-life [2], In their report, describing the isolation and sequence determination of BNP from porcine brain, Sudoh et al [ 12] also showed that this substance was as active as ANP in inducing relaxation of smooth muscle cells and hyotension in the anesthetized rat. These data have been con firmed by several animal studies [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], The cardiovascu lar effects of BNP in humans were investigated by Yoshi- mura et al [19], who administered synthetic human BNP (0.1 pg/kg-min for 30 min) to healthy subjects and pa tients with congestive heart failure. In healthy subjects, BNP infusion significantly increased the cardiac index and decreased PVR.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma levels of this hormone are higher than normal in several disease states, such as congestive heart failure [2], acute myocardial infarction [3], hypertension [4,5], chronic renal failure [6] and cirrhosis with ascites [7], Two studies [8,9] showed that the infusion of synthet ic human BNP, in order to increase its plasma concentra tions to the levels usually observed in heart failure (that is to the 'pathophysiological' range), markedly affects renal hemodynamics [9] and function [8,9] in healthy subjects, leading to an increase in urine flow rate and sodium excre tion. In both studies, systemic hemodynamics was not influenced by BNP infusion [8,9], examination, blood pressure, urinalysis, blood cell count, fasting serum glucose, BUN, creatinine, electrolytes, electrophoresis of se rum proteins, enzymes, electrocardiographic and echocardiographic findings were also normal.…”
Section: Introductionmentioning
confidence: 99%
“…In man, intravascular saline loading has no effect on plasma BNP concentrations [29], while an increase in dietary sodium stimulates BNP levels [30]. Furthermore, plasma levels of BNP respond to posture‐induced changes in central volume and fall, for instance, when the individual moves from the supine to the sitting position [27,31]. The observation that plasma levels of BNP are elevated in disease states which are associated with volume overload, such as heart failure and some forms of hypertension, are in line with the hypothesis that BNP levels reflect one's extracellular volume.…”
Section: Production Of Bnpmentioning
confidence: 99%
“…Brain natriuretic peptide (BNP) is a polypeptide hormone, also secreted by the heart [18], which is both structurally and functionally similar to ANP [19–21]. Although elevated plasma concentrations of ANP and BNP are reported in a similar spectrum of pathophysiological states in the nondiabetic population [22–26], little is known regarding plasma BNP concentrations in DM. One study has reported elevated plasma BNP concentrations in Type 2 DM subjects with microalbuminuria, but the elevated plasma BNP concentrations were interpreted as being secondary to renal dysfunction [27].…”
Section: Introductionmentioning
confidence: 99%